Anion Acceptors Dioxaborinane Contained in Solid State Polymer Electrolyte: Preparation, Characterization, and DFT Calculations. (14th June 2016) - Yuan, Ping; Cai, Chuanlin; Tang, Jiayong; Qin, Yuqi; Jin, Mengyuan; Fu, Yanbao; Li, Zhenhua; Ma, Xiaohua
Abstract : A novel dioxaborinane‐contained solid state polymer electrolyte poly((2‐phenyl‐1, 3, 2‐dioxaborolane‐4‐yl) methyl methacrylate) (P(GMMA‐PBA)) for symmetrical capacitors (SCs) is prepared through solution casting technique. Due to the effect of electron withdrawing of dioxaborinane groups and irregular distributed porous microstructures, the solid polymer electrolyte (SPE) exhibits an optimal ionic conductivity of 0.5 mS cm −1 at ambient conditions. The electronic properties of dioxaborinane groups and their interaction with anions of electrolyte salts are further studied with density functional theory calculations. SCs fabricated with this polymer film as electrolyte and reduced graphene oxide as electrodes provide a broad potential window of 2.5 V. The energy density of this capacitor ups to 22.49 Wh kg −1 with a power density of 6.34 kW kg −1 at 5 A g −1 . After 3000 charge–discharge cycles, the capacitance of the symmetrical SPE capacitor maintains 90% of its initial values. Abstract : Dioxaborinane‐contained polymer electrolytes are successfully prepared for supercapacitors through solution casting technique. Density functional theory calculations are conducted by electronic structure, basis set superposition error and natural bond orbital analyses to confirm the effect of coordination between heterocyclic borane groups and perchlorate ion. The obtained anion receptor polymer electrolytes present higher electrochemical properties compared to polyethylene oxide‐based electrochemical storage capacitors.